The Important Role of Customer Reviews and Testimonials on Instagram and WhatsApp in Building Consumer Trust in MUA Services - Husnul Mawaddah; Zulfikar Zulfikar; Intan Zuhra (Moneter: Jurnal Keuangan dan Perbankan, 2026)
This study aims to analyze the role of customer reviews and testimonials on Instagram and WhatsApp in building consumer trust toward YOERI Make-Up services. The study employed a descriptive qualitative approach using purposive sampling techniques. The research participants consisted of 30 customers who had used YOERI Make-Up services. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using the Miles and Huberman interactive analysis model, including data condensation, data display, and conclusion drawing. The findings indicate that customer reviews and testimonials play a significant role in shaping consumer trust before making purchasing decisions. The most trusted forms of reviews include videos of make-up results, before-after photos, customer documentation, and screenshots of customer conversations because they are perceived as more authentic and difficult to manipulate. Instagram functions as a visual platform for displaying portfolios, reviews, and testimonials, while WhatsApp Business serves as a direct communication medium that enhances consumer convenience and trust. The study further reveals that the higher the level of consumer trust established through reviews and testimonials, the greater the likelihood that consumers will choose YOERI Make-Up services. Therefore, customer reviews and testimonials represent effective digital marketing strategies for strengthening consumer trust.